2015
DOI: 10.5194/amt-8-3069-2015
|View full text |Cite
|
Sign up to set email alerts
|

Electron density profiles probed by radio occultation of FORMOSAT-7/COSMIC-2 at 520 and 800 km altitude

Abstract: Abstract. The FORMOSAT-7/COSMIC-2 (F7/C2) will ultimately place 12 satellites in orbit with two launches with 24-28.5 • inclination and 520-550 km altitude in 2016 and with 72 • inclination and 720-750 km altitude in 2018. It would be very useful for the community to construct the global three-dimensional electron density structure by simultaneously combining the two launch observations for studying ionospheric structure and dynamics. However, to properly construct the global electron density structure, it is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Although the TGRS orbit electron density and IVM ion density generally show a good agreement, it is a challenge to evaluate the accuracy of IVM ion density since the TGRS orbit electron density has systematic errors due to the spherical symmetry assumption. Therefore, observing system simulation experiments (OSSEs) are performed to assess the systematic errors in TGRS orbit electron density observations (e.g., Liu et al 2015, Chou et al 2017. Yue et al (2011) indicated that the solar activity would not influence the relative Abel errors of electron density.…”
Section: Observing System Simulation Experimentsmentioning
confidence: 99%
“…Although the TGRS orbit electron density and IVM ion density generally show a good agreement, it is a challenge to evaluate the accuracy of IVM ion density since the TGRS orbit electron density has systematic errors due to the spherical symmetry assumption. Therefore, observing system simulation experiments (OSSEs) are performed to assess the systematic errors in TGRS orbit electron density observations (e.g., Liu et al 2015, Chou et al 2017. Yue et al (2011) indicated that the solar activity would not influence the relative Abel errors of electron density.…”
Section: Observing System Simulation Experimentsmentioning
confidence: 99%
“…The constellation is primarily used to collect atmospheric data for weather forecasting, ionospheric, climate, and gravity studies [1][2][3][4]. The satellite has a design lifetime of 5 years, an orbital inclination of 24 degrees, an altitude of 550 km, and an orbit around the Earth of approximately 97 minutes [1,5]. Each of the six satellites is equipped with two POD antennas, the forward antenna (+ X POD antenna, in the direction of satellite ight) and the rear antenna (-X POD antenna, backward to the direction of satellite ight), and each satellite is equipped with a Tri-GNSS radio occultation receiver system (TGRS) receiver that can obtain GPS and GLONASS signals to achieve POD of COSMIC-2 [6-8].…”
Section: A Subsection Samplementioning
confidence: 99%
“…It is a continuation of COSMIC-1 mainly used to collect atmospheric data for weather prediction, ionosphere and gravity research [3,4]. COSMIC-2 constellation contains six satellites, the designed orbit inclination is 24 degrees with occultations primarily distributed from 45 • N and 45 • S, the designed life is 5 years, the initial orbit altitude is 750 km, and the final orbit is 525 km, and it takes about 100 min to fly around the earth per circle [1,5]. In order to realize the scientific function of the constellation and provide the basis for scientific data, each satellite is equipped with the advanced Tri-GNSS radio occultation (RO) system (TGRS) receiver, and its two orbit determination antennas are POD + X and POD − X respectively.…”
Section: Introductionmentioning
confidence: 99%